Parametric Study on Natural Period of Offshore Structures in Malaysian Waters - Mohd Wira, Saifuddin Azam (IRC, 2019)
Natural period or natural frequency is an important parameter in designing offshore structures. This project is proposed to study on the magnitude of changes of natural period, if there are any, and the factors contributing towards the changes. These changes may exist due to variations towards the system’s condition or its surrounding. This research will involve data from offshore platforms in Malaysian waters across 3 main water regions under the operation of PETRONAS. There are two main methods that will be executed for this project.